Acute Total Ulnar Collateral Ligament Injuries of Thumb - Primary Repair with Mini Soft Suture Anchor (JuggerKnot™) - Kara, A; Gülenç, B; Çelik, H; Kilinç, E; Çamur, S; Şener, B (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY We aimed to investigate the functional outcomes and complications of a new approach, the primary UCL repair using JuggerKnot™ Soft Anchor-1.0 mm Mini (Zimmer-Biomet). MATERIAL AND METHODS This study included a total of 12 patients with acute UCL injury who were operated with primary repair with JuggerKnot™ Soft Anchor-1.0 mm Mini between January 2012 and September 2016. All patients were operated on using the same surgical technique. The thumb pinch and grip strengths, articular range of motion, and Glickel functional score were recorded for all patients. The pinch grip strength and articular range of motion were compared with the intact side. Early and late postoperative complications were recorded. RESULTS The mean follow-up time was 22.2 months (range 6-54 months). The grip strength and the pinch strength were 94.3% and 92.27%, respectively, of the contralateral side. Articular range of motion attained the same level as the contralatereal side in all patients at the final visit, and no patient suffered from any complication. The patients returned to work at a mean of 5.45 weeks, and the Glickel score was good in 1 patient and excellent in the remainder 11 patients. CONCLUSIONS Surgical repair using the JuggerKnot™ Soft Anchor-1.0 mm is an effective alternative treatment method for acute total ulnar collateral ligament (UCL) rupture. Key words:ulnar collateral ligament, acute total injury, thumb, soft suture anchor, JuggerKnot™.
Keywords: Pinch Strength; Suture Anchors; Humans; Collateral Ligament, Ulnar; Thumb; následné studie; Hand Strength; Range of Motion, Articular; lidé; palec ruky; obnova funkce; síla špetkového úchopu; síla ruky; ortopedické výkony; kotvící implantáty; Recovery of Function; vnitřní postranní vaz; Orthopedic Procedures; ruptura; rozsah kloubních pohybů; Follow-Up Studies; Rupture